Pribumization: The Epistemology of Abdurrahman Wahid's Thought (Gus Dur) - Muhammad Misbakhul Munir (Pelopor Publikasi Akademika, 2022)
The pribumization of Islam of Gus Dur's thought is very important to be described in the world of education, in order to explain to the wider community, about the advantages of the development of Islam in Indonesia. With the aim, so that the public better understands the cultural Islam that exists in Indonesia, where Islam and culture cannot be separated from each other. This is in line with the motto of the Unitary State of the Republic of Indonesia, namely Bhineka Tunggal Ika, which means different, both ethnic, racial, religious, cultural, linguistic, but still one, namely Indonesia. The method used in writing this article is to use the literature study method, by reading several references both from books, journals and other articles related to the title above. In short, the pribumization of Islam is how Islam is used as a normative teaching, which comes from God and then is accommodated into a culture that comes from humans without losing its own identity, Islam remains with its Islamic and culture remains with its culture.